2015
DOI: 10.1016/j.procir.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Environmental Performance of Machine Tools – Case Studies Applying the ‘LCA to go’ Webtool

Abstract: A simple, sector specific webtool was developed within the EU funded 'LCA to go' project, to enable SMEs to perform first environmental assessments of their industrial machines and machine tools. The tool was applied together with several SMEs, sixteen of which provided feedback on their user experience, applicability, value of the results and future plans with the tool. The software flow of the webtool is presented together with a summary of the outcome of the case studies. Based on the feedback and the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“… Krautzera et al. (2015) submitted that with the use of IoTs and web based applications manufacturing activities can be enhanced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Krautzera et al. (2015) submitted that with the use of IoTs and web based applications manufacturing activities can be enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) Life cycle phases Exploratory Fourie and Tendayi (2016) A decision-making framework for effective maintenance management Life cycle costing Slapnik et al. (2015) To extend the life cycle assessment normalization factors Machine learning approach technique Krautzera et al. (2015) Application of the webtool Internet of Things (IoTs) and web-based applications Jiang et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LCA concluded that the most significant environmental impact of machine tools occurs during the use phase compared to other phases such us, construction, transport installation and dismantling [7]. [14] developed an enabling webtool to perform a sector specific life cycle based on environmental assessment. It provided tailor-made solutions to integrate simplified life cycle approaches into daily business process in machines tool sector.…”
Section: Background and Introductionmentioning
confidence: 99%